PENGARUH CITRA MEREK, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK J.CO ROXY SQUARE JEMBER - Valentha, Fangky Vedhia; Satoto, Eko Budi; Reskiputri, Tatit Diansari (Relawan Jurnal Indonesia, 2022)
This study aims to determine and analyze the effect of brand image, product quality and price on purchasing decisions of J.CO Roxy Square Jember products. This type of research is quantitative research. The population in this study are consumers who have purchased products and visited J.CO Roxy Square Jember. The sampling technique used purposive sampling method with a total sample of 90 people. The analytical method used in this study is using multiple linear regression analysis, with the help of SPSS 25 software. The test results in this study indicate that partially brand image, product quality and price variables have a positive and significant effect on purchasing decisions J.CO Roxy Square Jember .